1971
DOI: 10.1111/j.1476-5381.1971.tb07121.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of catecholamine depletion by reserpine in the heart of the toad (Bufo marinus)

Abstract: Summary1. The catecholamines in toad ventricle were adrenaline (90%) and noradrenaline (10%); there was no dopamine. 2. Phenoxybenzamine and tyramine stimulated the isolated heart and reduced the catecholamine content.3. Reserpine treatment of toads kept at 200 C did not affect the adrenaline but reduced the noradrenaline content of the ventricle. 4. At 370 C, reserpine caused depletion of both adrenaline and noradrenaline, and the stimulant actions of phenoxybenzamine and tyramine were lost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…It has been reported that reserpine, even in high doses, does not cause depletion of catecholamines from tissues of the toad (NAYLER, 1963;BOYD et aI., 1964); however, when the body temperature of the toad is raised, reserpine becomes effective in causing almost complete loss of cardiac catecholamines (CHANG and RAND, 1971).…”
Section: Effects Of Reserpine On Levels Of Catecholamines and Sementioning
confidence: 98%
“…It has been reported that reserpine, even in high doses, does not cause depletion of catecholamines from tissues of the toad (NAYLER, 1963;BOYD et aI., 1964); however, when the body temperature of the toad is raised, reserpine becomes effective in causing almost complete loss of cardiac catecholamines (CHANG and RAND, 1971).…”
Section: Effects Of Reserpine On Levels Of Catecholamines and Sementioning
confidence: 98%